2015
DOI: 10.3748/wjg.v21.i16.4864
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory microenvironment and expression of chemokines in hepatocellular carcinoma

Abstract: These findings suggest that CXCL1 plays a critical role in tumor growth and may serve as a potential molecular target for use in HCC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Furthermore, it is worth pointing out that CCL2, a chemokine considered to be a central coordinator of hepatocyte-mediated inflammation, 38 showed decreased expression in DEGFR tumors. Finally, CXCL1, considered a critical player in both inflammation and tumor growth in HCC, 39 presented significantly decreased mRNA levels in DEGFR tumoral and nontumoral areas. Regardless of the mechanism and considering together our results and others in the literature, there is no doubt that one of the most essential functions of the EGFR pathway during hepatocarcinogesis should be regulation of inflammation addressed by parenchymal and/or nonparenchymal cells.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it is worth pointing out that CCL2, a chemokine considered to be a central coordinator of hepatocyte-mediated inflammation, 38 showed decreased expression in DEGFR tumors. Finally, CXCL1, considered a critical player in both inflammation and tumor growth in HCC, 39 presented significantly decreased mRNA levels in DEGFR tumoral and nontumoral areas. Regardless of the mechanism and considering together our results and others in the literature, there is no doubt that one of the most essential functions of the EGFR pathway during hepatocarcinogesis should be regulation of inflammation addressed by parenchymal and/or nonparenchymal cells.…”
Section: Discussionmentioning
confidence: 97%
“…the carcinogenesis and progression of HCC (8,19,20). IL-32 is known as a pro-inflammatory cytokine since it enhances the production of IL-1β and TNFα (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…A progressive increase in HCC-related mortality has been observed in the US and Western Europe (5)(6)(7). Accumulating evidence has revealed that inflammatory-related cytokines participate in the carcinogenesis and progression of HCC (8). Research has revealed that higher expression of interleukin-32 (IL-32), a novel pro-inflammatory cytokine, is detected in HCC (9).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we also found perforin deficiency increased IFN-g secretion in CD8 T cells, which may also contribute to the polarization of monocytes to the M1 phenotype. Moreover, compared with hepatic CD8 T cells from the WT group fed the MCD diet, CD8 T cells from the steatotic livers of Prf1 null mice express genes associated with the recruitment of monocytes such as CXCL3 at high levels; CXCL3 was reported to be involved in monocyte recruitment in the inflammatory microenvironment (25,26). Thus, perforin regulated monocyte accumulation and inhibited the monocyte-induced inflammation in the liver mainly through CD8 T cells during NASH development.…”
Section: Discussionmentioning
confidence: 99%